Discrimination of Voiced Plosives Using Transition Properties of The LPC Cepstrum Parameters - Yamashita, Y; Yanagida, M; Mizoguchi, R; Kakusho, O (Canadian Acoustics, 2022)
In this paper, a discrimination method of voiced plosives is proposed using two sets of parameters, one, that describes the transition of acoustic parameters by fitting their transition loci with regression lines and the other, the acoustic parameters themselves at the beginning point of the transition. The gradient of the regression lines is found to be effective for discriminating among voiced plosives.